Sexual Educational Values for Teenagers and the Role of Parents in Juno Movie - Tri Setianingsih; Bq Zuhrotun Nafisah (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
This Study aims to determine the values of sexual education and the role of parents in “Juno” movie. The object of this research was the values of sexual education and the role of parents. This research method used was descriptive qualitative. This technique of data collection used were documentation, watching, re-watching, identification. The data analysis technique used in this research was the Milen and Huberman model method: data reduction, data display, conclusions drawing/verification. Researcher found the values of sexual education and the role of parents in Juno movie. The results of this study found 5 values of sexual education: keep yourself from lust for the opposite sex, there will be a negative risk that will be accepted, to tell the dangers of abortion, teach to be responsible for yourself, impact of early pregnancy on teenagers and 2 roles of parents in Juno movie: protect, support, look after and help Juno solve the serious problem she faced, reminds Juno of the mistake she made.